2014
DOI: 10.1017/jfm.2014.303
|View full text |Cite
|
Sign up to set email alerts
|

Critical layer and radiative instabilities in shallow-water shear flows

Abstract: In this study a linear stability analysis of shallow water flows is undertaken for a representative Froude number F = 3.5. The focus is on monotonic base flow profiles U without an inflexion point, in order to study critical layer instability (CLI) and its interaction with radiative instability (RI). First the dispersion relation is presented for the piecewise linear profile studied numerically by Satomura (1981) and using WKBJ analysis an interpretation given of mode branches, resonances and radiative instabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 39 publications
7
13
0
Order By: Relevance
“…The energy of normal modes can concentrate within the critical level, as further described in Nguyen et al (2012) or Riedinger & Gilbert (2014). In our study, we show that the presence of the critical level for mode 2 induces an intense stretching of the flow S. The latter is defined as the sum of the strain and the shear:…”
Section: Critical Level Computationsupporting
confidence: 60%
See 1 more Smart Citation
“…The energy of normal modes can concentrate within the critical level, as further described in Nguyen et al (2012) or Riedinger & Gilbert (2014). In our study, we show that the presence of the critical level for mode 2 induces an intense stretching of the flow S. The latter is defined as the sum of the strain and the shear:…”
Section: Critical Level Computationsupporting
confidence: 60%
“…At the beginning of the simulation, transient perturbations occur in the core of the eddy, mostly stemming from the initial adjustment of the eddy. They are evanescent and rapidly decay (Riedinger & Gilbert, 2014). However, during the first 20 days, their energy has similar magnitude to that of the unstable mode 2.…”
Section: Journal Pre-proofmentioning
confidence: 94%
“…This can be understood easily for the hydrodynamic case : determines the strength of the singularity at , and the singularity becomes removable if is absent. Similar arguments have also been given by Riedinger & Gilbert (2014).…”
Section: The Asymptotic Analysissupporting
confidence: 86%
“…Candelier, Le Dizès & Millet (2012) showed that an inflection-free boundary layer profile becomes unstable with respect to an inviscid 'radiative instability' as soon as there is an angle between the directions of shear and stratification, the instability being the strongest for an angle of π/2, that is for a vertical wall. This instability, which results from the coupling between shear and internal waves, has been obtained in other contexts: shallow water flows (Satomura 1981;Balmforth 1999;Riedinger & Gilbert 2014), compressible flows (Mack 1990;Parras & Le Dizès 2010) and rotating flows (Riedinger, Le Dizès & Meunier 2010. It has often been associated with a phenomenon of resonant over reflection (McIntyre & Weissman 1978;Grimshaw 1979;Lindzen & Barker 1985), negative energy waves (Kopev & Leontev 1983) or spontaneous wave emission (Plougonven & Zeitlin 2002;Le Dizès & Billant 2009).…”
mentioning
confidence: 79%